Optimization of Polymer Nanocomposite Properties 2010
DOI: 10.1002/9783527629275.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in Polymer Nanocomposites

Abstract: Over the past decade, polymer nanocomposites have been a topic of great interest to research groups in both pure and applied materials science [1 -4] . These nanocomposites are two -phase materials wherein a fi ller with at least one dimension in the range of 1 to 100 nm is dispersed in the polymer matrix. Various nanofi llers such as carbon nanotube s ( CNT s), inorganic nanoparticles, or layered silicates such as clay are used. These nanocomposites show remarkable property improvements as compared to virgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 140 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…Polymer nanocomposites are a rapidly evolving class of relatively new materials finding applications in soft tissue engineering (TE) (Jog 2006). Advantages include a significant improvement in mechanical properties (El-Fray and Boccaccini 2005;Liu et al 2008) as well as enhanced cellular adhesion (Webster and Smith 2005;Bacakova et al 2007) and higher cytocompatibility than composites containing conventional micrometer particles (Webster et al 2003;Webster and Smith 2005;Mei et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites are a rapidly evolving class of relatively new materials finding applications in soft tissue engineering (TE) (Jog 2006). Advantages include a significant improvement in mechanical properties (El-Fray and Boccaccini 2005;Liu et al 2008) as well as enhanced cellular adhesion (Webster and Smith 2005;Bacakova et al 2007) and higher cytocompatibility than composites containing conventional micrometer particles (Webster et al 2003;Webster and Smith 2005;Mei et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the incorporation of nanoparticles (NPs) into polymer matrices can have a large impact on their mechanical, electrical, optical, and thermal properties. Semicrystalline polymers comprise approximately 70% of commercial polymers, and their properties sensitively depend on their morphology . An easy way to modify this morphology is to add NPs to the polymer, and therefore, over the last few decades, there has been extensive research on this topic, for example, crystalline morphologies, ultimate crystallinity, rates of nucleation and growth, and interaction mechanisms and how they are affected by NP addition. Zhao et al , found that a critically important quantity in this situation is the mobility of the NPs relative to the spherulitic growth rates. For large enough spherulitic growth rates, the NPs are trapped and engulfed by the growing polymer spherulites.…”
Section: Introductionmentioning
confidence: 99%
“…Industries have been shifting into sustainable alternatives, and the use of biodegradable/biocompatible materials has been the focus of various groups. Poly­(ethylene oxide) (PEO) is a biocompatible, semicrystalline polymer used in various applications: solid electrolytes, , for drug delivery, , in biomedical scaffolds, and for polymer fabrication. , An easy way to create robustly advanced materials from such a polymer is through nanoparticle (NP) incorporation. , Since PEO is a semicrystalline polymer with a high degree of crystallinity, the corresponding nanocomposite and blend properties are highly affected by changes in the crystallization kinetics and the final semicrystalline PEO morphology. Thus, many studies have focused on understanding how NP addition affects crystallization kinetics this topic is precisely the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%